Atomic physics: A new spin on magnetometry - Budker, Dmitry (Nature (London), 2003)
On page 596 of this issue, I. K. Kominis and colleagues report on a new type of atomic magnetometer that achieves unparalleled sensitivity to small magnetic fields as well as millimetre-scale spatial resolution. This device may open up exciting frontiers in diverse areas of science, ranging from biomagnetic imaging to testing fundamental symmetries of nature. The most sensitive magnetometers of this type use vapours of alkali atoms, such as potassium, that have a single unpaired electron. When the atoms are subject to a beam of resonant, polarized light (such as from a laser), these unpaired electrons are excited to a higher energy level, but subsequently return to their ground state by spontaneously emitting the energy or losing it through collisions. This 'pumping' process transfers the polarization of the incoming light to the atoms, affecting the direction of their electronic spins. But imparting polarization to the atoms like this, in turn, modifies the optical properties of the atomic medium; for example, it changes the way it absorbs laser light. The sensitivity of such a system to an external magnetic field comes from the torque that the field exerts on the magnetic moments of the atoms, which are themselves proportional to the electron spin.